2006
DOI: 10.1002/qre.829
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate statistical process control charts: an overview

Abstract: In this paper we discuss the basic procedures for the implementation of multivariate statistical process control via control charting. Furthermore, we review multivariate extensions for all kinds of univariate control charts, such as multivariate Shewharttype control charts, multivariate CUSUM control charts and multivariate EWMA control charts. In addition, we review unique procedures for the construction of multivariate control charts, based on multivariate statistical techniques such as principal components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
313
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 506 publications
(352 citation statements)
references
References 189 publications
2
313
0
9
Order By: Relevance
“…The results were computed based on the correctly classified patterns. The results support the conclusion that the mean shift with larger magnitudes can be identified more quickly with shorter ARL 1 .…”
Section: A Average Run Lengthssupporting
confidence: 86%
See 1 more Smart Citation
“…The results were computed based on the correctly classified patterns. The results support the conclusion that the mean shift with larger magnitudes can be identified more quickly with shorter ARL 1 .…”
Section: A Average Run Lengthssupporting
confidence: 86%
“…Numerous multivariate statistical process control (MSPC) schemes have been proposed for monitoring and diagnosing multivariate process mean shift. A review on traditional MSPC charts and multivariate statistical techniques can be found in [1]. The traditional MSPC charts refer to the T 2 , multivariate cumulative sum (MCUSUM) and multivariate exponentially weighted moving average (MEWMA), whereas the multivariate statistical techniques refer to the principal component analysis (PCA) and partial least square (PLS).…”
Section: Introductionmentioning
confidence: 99%
“…In quality prediction, PCA is used to define the new set of variables by transforming several correlated manufacturing operation variables. PCA is used to develop a prediction model from a historical dataset when product quality data are not available [30]. The product quality is monitored based on the transformed manufacturing operation variables.…”
Section: Related Workmentioning
confidence: 99%
“…For this reason, in the industry, there are many situations in which the simultaneous monitoring or control of two or more related process characteristics is necessary [8] [9]. In the literature, SPM of multiple variables is collectively known as multivariate SPM [8].…”
Section: Introductionmentioning
confidence: 99%
“…Practitioners using SPM are forced to interpret a huge amount of quality indicators related to each prod-uct characteristic and thus, they encounter diculties when monitoring multivariate production processes because monitoring all quality characteristics independently can be very misleading [8].…”
Section: Introductionmentioning
confidence: 99%